High-strength gypsum binder with improved water-resistance coefficient derived from industrial wastes; Waste Management & Research; Vol. 43, iss. 2 - Kamarou M. Maksim; Moskovskikh Dmitry D.; Kuskov K. Kirill; Yudin S. Sergey; Akinwande A. A. Abayomi Adewale; Smorokov A. A. Andrey Arkadievich; Özkılıç Ya. O. Yasin Onuralp; Abdulwahid M. Ya. Mohanad Yaseen; Bhowmik A. Abhijit; Romanovskaia E. Elena; Korob N. Natalia; Paspelau A. Andrei; et al. (2024, 2024)
Title screen